RAPID ASESMEN KERUSAKAN BANGUNAN PASCA GEMPA BUMI DI SEKITAR MASJID AT-TAQARRUB, TRIENGGADING, PIDIE JAYA, ACEH - Aldrin Febriansyah (UNHI Press, 2020)
The earthquake that occurred on 7 December 2016 with a magnitude of 6.4 SR in Pidie Jaya District, Aceh has resulted in many material and immaterial losses. Where many facilities and infrastructure are damaged, buildings are not multi-storey to high-rise buildings. One of them is a residential area around the At-Taqarrub mosque, which is in the Keude area, Trienggading sub-district, Pidie Jaya district. At-Taqarrub Mosque is one of the worship facilities that is heavily damaged and cannot be repaired. In the area only the At-Taqarrub mosque was the only building that collapsed, while the surrounding buildings were still standing with various kinds of damage. This journal is to find out the results of rapid assessment of the level of damage to buildings against structures and building materials around the At-Taqarrub mosque. The method used is the method of mapping and direct survey of the surrounding buildings and then determine the level of damage to the structural components and building architecture. The results of this study indicate various levels of post-earthquake building damage that occur and provide recommendations for buildings damaged in the earthquake in Pidie Jaya in particular and throughout Indonesia in general.